The Reconstruction of The Madrasah Curriculum Based on Spiritual Character at MAN Bojonegoro - Wahid, Abdul (Didaktika Religia, 2023)
Character education is not only related to behavior but also to the knowledge and skills of students. Character education is a special requirement to achieve academic results. However, the failure of formal education to integrate character education into the curriculum raises problems, such as immoral problems. In response to the failure of integration, MAN 1 and MAN 2 Bojonegoro reconstructed by incorporating elements of spirituality-based character into their curriculum. This research is a multi-case study using qualitative methods with a descriptive-analytical approach. The results of the study revealed; First, the process of integrating elements of spirituality as character education into the MAN 1 and MAN 2 Bojonegoro curriculum, through three stages; 1) Planning. Includes determining the basis of spiritual values, academic culture, and teaching materials; 2) Implementation. Includes extracurricular and extracurricular activities. But in MAN 2 Bojonegoro, spiritual characters are not internalized into intracurricular activities; 3) Evaluation. Includes tests and persuasion to students. Second, the internalization of reinforcement character education into the curriculum includes two things; 1) a Comparative system, which juxtaposes teaching materials with elements of reinforcement character education; and 2) an Analysis system, which is to see the needs and vision of madrasah in the future. The implication of this research is the emergence of awareness throughout formal institutions to carry out a total reconstruction of their curriculum. That is to integrate spiritual character as character education into the base, goals, and strategies of education, to teaching materials.